The adaptation of the cardiovascular system of children of primary school age to the teaching load (Experimental biology, 2015)
Extent of reaction of a warm rhythm at children of the third and second classes on school academic loads is investigated. It is established that the academic load in volume of 4 lessons in day causes tension of mechanisms of regulation of warm activity which exceeds average values several times in some children and indicates the need of an individual approach to training
Keywords: adaptation; Fashion (Maud); Amplitude of fashion (AMO); index of vegetative balance (IVR0